Analysis of Afghanistan’s Trade Laws in Light of International Instruments - Amani, Aburagheb; Noori, Mohammad Ishaq (Journal of Law, Society and Policy Review, 2025)
Being among the drivers of economic development, international trade will no doubt catalyze the rate of economic growth, promote trade exchange, and encourage investment. For a country like Afghanistan, which direly needs to develop economically and get properly positioned within the international trade system, there is definitely no denying the need to align domestic laws with international frameworks and standards, especially those of the World Trade Organization. The current paper analyzes the legal framework of trade in Afghanistan, including the Constitution, the Commercial Code, the Law on Limited Liability Companies, and the Private Investment Law. It underlines that while these laws partially comply with the WTO principles, the effective use of the advantages of accession to the WTO requires deeper legal reforms, increased transparency, and the abolition of non-tariff barriers. Key recommendations highlight the need for further harmonization of domestic law with international agreements, enhancing mechanisms for enforcement, fighting administrative corruption, and winning investor confidence. Success in Afghanistan's exploiting the WTO membership is contingent upon high political will, international cooperation, and effective support for legal and economic reforms. The realization of these objectives will ensure Afghanistan's sustainable economic development and its integration into world trade.